2010
DOI: 10.1007/s11064-010-0165-8
|View full text |Cite
|
Sign up to set email alerts
|

Aging and Lateralization of the Rat Brain on a Biochemical Level

Abstract: It has been suggested that the lateralization of the human brain underlies hemispheric specialization and that it can be observed also on a biochemical level. Biochemical laterality appears to be a basis of volumetric or functional asymmetry but direct relationships among them are still unclear. Moreover, age-related differences between the right and left hemispheres are not well documented in various rat strains. In the current study, biochemical markers sensitive to Alzheimer disease (activities of high-affi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
2

Year Published

2011
2011
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 23 publications
6
15
2
Order By: Relevance
“…Moreover, no individual young markedly lateralized (defined by an index of laterality greater than ±0.100) rat was identified. No asymmetrical differences in nNOS or eNOS activity were observed globally; however, in contrast to the NMDAR subunits, we found some lateralized individuals [namely, one-third of animals displayed marked R/L asymmetry of globally unlateralized nNOS/iNOS, one-third presented opposite L/R laterality, and only one-third was unlateralized, in accordance with our previous study (Krištofiková et al, 2010)]. On the other hand, young Sprague-Dawley males displayed pronounced R/L laterality in iNOS activity, similar to Wistar and Long Evans strains (Krištofiková et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, no individual young markedly lateralized (defined by an index of laterality greater than ±0.100) rat was identified. No asymmetrical differences in nNOS or eNOS activity were observed globally; however, in contrast to the NMDAR subunits, we found some lateralized individuals [namely, one-third of animals displayed marked R/L asymmetry of globally unlateralized nNOS/iNOS, one-third presented opposite L/R laterality, and only one-third was unlateralized, in accordance with our previous study (Krištofiková et al, 2010)]. On the other hand, young Sprague-Dawley males displayed pronounced R/L laterality in iNOS activity, similar to Wistar and Long Evans strains (Krištofiková et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…We therefore recommended their use in animal models of various diseases that are accompanied by alterations in brain asymmetry. Knowledge of disease-mediated changes occurring in the human R and L hemisphere separately as well as that of brain lateralization of applied control animals (there are differences between mice and rats and also among various rodent strains) is necessary in validating animal models in this way (Krištofiková et al, 2004, 2008, 2010). Moreover, we have repeatedly found a very similar degree of brain asymmetry on a biochemical level in the hippocampus and cortex, two of the most asymmetrical brain regions (Krištofiková et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The right-specific laterality has also been demonstrated in rat studies of stress-related processes where medial prefrontal cortex output neurons demonstrated an intrinsic right brain specialization in both neuroendocrine and autonomic activation [34]. These differences have been proposed to have a biochemical basis [35].…”
Section: Discussionmentioning
confidence: 80%
“…Hemispheric asymmetry is however much less documented in animal models. Biochemical markers were studied (Ramírez et al, 2004) and L/R asymmetry of cholinergic markers and their age dependence were found in various brain structures (Kristofiková et al, 2010;Kristofikova et al, 2004). We are not aware of any functional imaging study investigating response asymmetry in rats.…”
Section: Introductionmentioning
confidence: 99%